253=-2-5(7k+5)

Simple and best practice solution for 253=-2-5(7k+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 253=-2-5(7k+5) equation:


Simplifying
253 = -2 + -5(7k + 5)

Reorder the terms:
253 = -2 + -5(5 + 7k)
253 = -2 + (5 * -5 + 7k * -5)
253 = -2 + (-25 + -35k)

Combine like terms: -2 + -25 = -27
253 = -27 + -35k

Solving
253 = -27 + -35k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '35k' to each side of the equation.
253 + 35k = -27 + -35k + 35k

Combine like terms: -35k + 35k = 0
253 + 35k = -27 + 0
253 + 35k = -27

Add '-253' to each side of the equation.
253 + -253 + 35k = -27 + -253

Combine like terms: 253 + -253 = 0
0 + 35k = -27 + -253
35k = -27 + -253

Combine like terms: -27 + -253 = -280
35k = -280

Divide each side by '35'.
k = -8

Simplifying
k = -8

See similar equations:

| n^2-13n+50=0 | | -z+4=26 | | -3(8y-5)=4(1-7y)+14 | | Vf=0+0*20 | | 100x+90-x=99 | | 1+3n=1+3n | | 12+2[6+7(x+1)]=0 | | (X+21)+(x+61)+(X+23)=180 | | 1/4x^4-4 | | x-6=4x-2x-9 | | -21x+18x=3(-6-2x) | | 2.9x+4.5x= | | 2b(2a-x)=x(b-a)+a(x+b) | | X^2/3=10 | | 5(x-7)+6=5x-23 | | (2x+3)*(4x+7)=8x^2-5 | | X+(X+55)+(X+38)=180 | | 14/5x−14=4/5x−7/4 | | 12=7m-1+6m | | U=2a+2b | | X+3x-4=5(x+2) | | 6y-2=20 | | 18(2x+6)=6(3x+30) | | 40p-5=-5p-5 | | lne^4/5 | | 3x+7+5x=11+4x+8 | | 2x-6x=-2x | | 26+X^2=90 | | 6x^3+2x^2=10x-8 | | 5.8(x-4)=0.2x+24.8 | | -d+5=20 | | -6=1/3x-4 |

Equations solver categories